Role Of Foliar Spray With Selenium And Urea On Growth, Flowering, And Yield Of Strawberry (Fragaria X Ananassa Duch.) Cv. Camarosa - Ahmad T.Khalil; Prof. Dr. Jassim M. A. Al-Aareji (Zien Journals, 2022)
The effect of foliar spray with Selenium at three levels (0, 3 and 6 mg Se. L-1) and urea at two levels (0% and 1%), each alone or in combination, were studied on the growth, flowering, fruit set and yield of strawberry plants (Fragaria x ananassa Duch.) cv. Camarosa, which were planted in an unheated greenhouse/Department of Horticulture and Landscape Design/College of Agriculture and Forestry / University of Mosul during the growing season 2020-2021. The results obtained showed that the foliar spray with Selenium, especially at a concentration of 6 mg Se. L-1 and 1% urea, each separately or in combination, significantly increased all study parameters. The best treatments were the spraying strawberry plants cv. Camarosa with 6 mg Se.L-1 + 1% urea with each other, which recorded a significant superiority of all studied traits(leaves Chlorophyll, plant leaves area, number of flowers per plant, fruits set percentage, number of fruits per plant, fruit weight, plant yield, fruits yield per hectare) over most interaction treatments, including control treatment.
Keywords: Selenium; Urea; Strawberry; Camarosa